Preliminaries - Blanco-Mesa, Fabio (Unidad Editorial UPTC, 2021)
Revista Inquietud Empresarial / Escuela de Administración de Empresas /Facultad de Ciencias Económicas y Administrativas Universidad Pedagógica y Tecnológica de Colombia. Tunja - Boyacá́ - Colombia Vol. I (2) (1988) - Vol. XXI (2) (2021). Tunja: UPTC, 1988 - 2020. Semiannual ISSN 0121-1048 Printed, ISSN 2422-3220 On-line Legal Status CopyrightRevista Inquietud Empresarial© belongs to the School of Business Administration, Faculty of Economics and Administrative Sciences, Universidad Pedagógica y Tecnológica de Colombia. The publication rights of the articles that appear in each edition belong to the School of Business Administration of the Universidad Pedagógica y Tecnológica de Colombia. The reproduction and citation of the material contained in the journal is authorized, as long as the following is explicitly indicated: name of the journal, name of the author(s), year, volume, number and pages of the source article. Mention of commercial products or firms in the journal does not imply a recommendation or endorsement by the University or the School; the use of such products must adhere to the recommendations on the labels. Translated with www.DeepL.com/Translator (free version)